The determinants of housing price in selected developed and developing economies - Ch’ng, Pei Shan; Chen, Yi How; Chong, Kah Yee; Ong, Lei Xian (2022)
This study attempts to assess the determinants of the housing price in selected developed and developing economies. As we all know, RRPPI is a broad measure of the movement of single-family house prices. It can also be used as an analytical tool to estimate mortgage default rates, prepayment rates, and changes in housing affordability. The rise and fall of housing prices will have a major impact on the economy. The rise in housing prices usually creates more jobs, stimulates confidence, and encourages consumer spending. Moreover, most of the country’s RRPPI began to fluctuate, these high-volatility changes provide an opportunity to carry out this research, which is to use the yearly data to test the factors affecting the RRPPI from 2004 to 2018. In addition, panel data estimation is used to study the relationship between independent variables. The independent variables are GDP, inflation rate, unemployment rate, population, and construction cost. The dependent variable is the Real Residential Property Price Index. It focuses on the selected developed and developing economies such as Australia, Canada, Germany, Iceland, New Zealand, Switzerland, Indonesia, Malaysia, Peru, Russia, Serbia, and Thailand. Lastly, the empirical results for selected developed economies showed that the population influences housing prices positively and significantly. Besides, it revealed that the inflation rate, unemployment rate, and construction cost influence the housing prices negatively and significantly. Then, the GDP has no significant impact on the housing prices there. On the other hand, the empirical results for the selected developing economies revealed that the GDP and unemployment rate influence the housing price positively and significantly. Besides, the results showed that the construction cost influences housing price negatively and significantly. However, the inflation rate and population have no significant impact on the housing prices there.